(untitled) (Global Journal of Human-Social Science, 2023)
Complementary learning system believes that the acquisition and consolidation of new information is a relatively slow process Contrary to the traditional theory recent studies have shown that new words learned by fast mapping FM paradigm can be rapidly integrated into neocortical memory networks inducing neural mechanisms different from the complementary learning system However factors affecting rapid cortical integration through FM are still under debate This study thus explored the influences of semantic referent on L2 English vocabulary learning in the FM paradigm Fifty participants were randomly assigned to the fast mapping or the incidental encoding learning condition and completed three vocabulary tests shortly after learning and again about 24 hours later